Discrepancies in Describing Pain: Is There Agreement Between Numeric Rating Scale Scores and Pain Reduction Percentage Reported by Patients with Musculoskeletal Pain After Corticosteroid Injection?. Issue 5 (26th February 2015) - Cushman, Daniel; McCormick, Zachary; Casey, Ellen; Plastaras, Christopher T
Abstract Objective Pain intensity is commonly rated on an 11‐point Numerical Pain Rating Scale which can be expressed as a calculated percentage pain reduction (CPPR), or by patient‐reported percentage pain reduction (PRPPR). We aimed to determine the agreement between CPPR and PRPPR in quantifying musculoskeletal pain improvement at short‐term follow‐up after a corticosteroid injection. Design Retrospective cohort study. Setting Urban, academic, physical medicine, and rehabilitation outpatient interventional musculoskeletal and spine center. Methods The agreement between CPPR and PRPPR was determined by concordance correlation coefficient (CCC) in subjects who had experienced improvement in musculoskeletal or radicular pain 3 weeks after a first‐time injection at our clinic. Subjects who experienced unchanged pain (PRPPR = 0) were compared to CPPR with paired t‐test. Results We examined 197 subjects with greater than 3/10 pain who underwent first‐time fluoroscopic‐guided corticosteroid injections. Ninety‐three subjects reported higher PRPPR than CPPR values, and 41 subjects reported higher CPPR values. The CCC between CPPR and PRPPR was 0.44 (95% CI 0.35–0.54), with a precision of 0.54 and an accuracy of 0.81, and 95% limits of agreement ranging between −41% and +73%. Values for CCC, precision, and accuracy were higher for males compared to females and were highest in the youngest age group (18–40) and lowest in the middle age group (41–60). Conclusions PRPPR may not agree with CPPR at 3 week follow‐up, as these individuals tend to report a higher estimated percentage improvement compared to the value calculated from their pain scores.